2006
DOI: 10.1089/ten.2006.12.1775
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte Phenotype in Engineered Fibrous Matrix Is Regulated by Fiber Size

Abstract: A biomaterial scaffold acting as a functional substitute for the native extracellular matrix provides space for cell accommodation. In this study, we seeded chondrocytes, isolated from 4- to 6-month-old calves, in 2 types of poly(L-lactide) scaffolds, composed of micro- and nanofibers, and compared the effects on cellular activities. Scanning electron microscopy revealed a well-spread morphology for chondrocytes grown on microfibers. In contrast, chondrocytes on the nanofibers were found to have a rounded morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(131 citation statements)
references
References 39 publications
3
127
0
1
Order By: Relevance
“…Besides chemical properties, it has been established that the size of nanofibers regulates adhesion, proliferation, and differentiation of NIH-3T3 fibroblasts, chondrocytes, and osteoblasts. [27][28][29][30] The representative mechanical parameters of CPSAPAni/PLCL nanofibers calculated from stress-strain curves are presented in Figure 3. Overall, PACL-1 shows the highest tensile strength, Young's modulus, and elongation at break.…”
Section: Resultsmentioning
confidence: 99%
“…Besides chemical properties, it has been established that the size of nanofibers regulates adhesion, proliferation, and differentiation of NIH-3T3 fibroblasts, chondrocytes, and osteoblasts. [27][28][29][30] The representative mechanical parameters of CPSAPAni/PLCL nanofibers calculated from stress-strain curves are presented in Figure 3. Overall, PACL-1 shows the highest tensile strength, Young's modulus, and elongation at break.…”
Section: Resultsmentioning
confidence: 99%
“…Electrospun membranes possess high porosity, large surface area and maximum interconnectivity of pores with a non-woven nanofibrous structure [17][18][19]. The fibers within the resulting scaffold more closely mimic the size and structure of the native extracellular matrix than other previously investigated scaffolds, which can lead to beneficial cellular interactions [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies demonstrated that the maintenance of a chondrocytic phenotype is enhanced on nanofi bers with dimensions similar to the native ECM, e.g., in the nano region, when compared to micro-sized fi bers. [ 41 ] A number of preceding studies, including ours, were focused on mimicking the fi brous protein structure of ECM utilizing different polymer-based fi brous scaffolds. [ 42 ] Up to this point, pellet cultures-thought of as the golden standard in cartilage engineering [ 35 ] was considered to work as positive control.…”
Section: Earlymentioning
confidence: 99%